1D and 2D phase gradient perforated dielectric reflective surfaces at mmWave. Issue 4 (14th December 2017) - Al-Nuaimi, Mustafa K. Taher; Hong, Wei; Gao, Xiqi
Abstract : This paper presents the design of all dielectric non-absorptive phase gradient reflective surfaces that can be used to manipulate the reflected electromagnetic waves at millimeter-wave regime. Compared with a bare perfect electrical conductor reflector which obeys the classical Snell's law of reflection, the presented design can effectively alter both the shape and level of the backscattered energy and thus radar cross section (RCS) reduction is achieved in the specular direction. One- and two-dimensional phase gradient reflective dielectric surfaces of phase change about 72° across their apertures are designed and their ability to manipulate the reflected waves under normal incidence are investigated both by means of full-wave simulations and experimentally tested for validation. More than 6 dB of specular RCS reduction is achieved from about 66.5–78.2 GHz.